TA’LIM FANLARINI INTEGRATSIYALASHDA ELEKTRON TA’LIM TEXNOLOGIYALARINI QO‘LLASH VA O‘QUVCHILARNING MOTIVATSIYASINI OSHIRISH USULLARI - Annayeva, M.R. (SCIENCE and SOCIETY, 2025)
In this article is considered the problems of using e-learning technologies and increasing student motivation in the integration of educational disciplines, the most pressing issues of the modern education system. In addition, innovative technologies are considered used in education, including online platforms, mobile applications and interactive programs, the possibilities of tools to make the educational process more effective and interesting, ways to increase students’ learning motivation through the integration of e-learning technologies.